2014
DOI: 10.5194/amt-7-537-2014
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of observed microwave signatures from ground dual polarization radar and space multi-frequency radiometer for the 2011 Grímsvötn volcanic eruption

Abstract: Abstract. The important role played by ground-based microwave weather radars for the monitoring of volcanic ash clouds has been recently demonstrated. The potential of microwaves from satellite passive and ground-based active sensors to estimate near-source volcanic ash cloud parameters has been also proposed, though with little investigation of their synergy and the role of the radar polarimetry. The goal of this work is to show the potentiality and drawbacks of the X-band dual polarization (DPX) radar measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…R HV (unitless) is the modulus of the correlation coefficient between horizontal-polarized (H) and vertical-polarized (V) signals, and it describes the target heterogeneity within the radar resolution cells, while W (m 2 /s 2 ) is an indication of the diversity of the particle radial velocities. For a robust theoretical background in the meaning of radar variables, see Bringi et al [26], and for exploitation of radar polarimetry in relation to ash clouds, see Vulpiani et al [27], Montopoli et al [28] and Crouch et al [29].…”
Section: X-band Radarmentioning
confidence: 99%
See 1 more Smart Citation
“…R HV (unitless) is the modulus of the correlation coefficient between horizontal-polarized (H) and vertical-polarized (V) signals, and it describes the target heterogeneity within the radar resolution cells, while W (m 2 /s 2 ) is an indication of the diversity of the particle radial velocities. For a robust theoretical background in the meaning of radar variables, see Bringi et al [26], and for exploitation of radar polarimetry in relation to ash clouds, see Vulpiani et al [27], Montopoli et al [28] and Crouch et al [29].…”
Section: X-band Radarmentioning
confidence: 99%
“…The former include C a , M a and R e , while the latter include h ct and ∆h ct . The volcanic ash radar retrieval (VARR) procedure, developed in Marzano et al, 2006 [30], and subsequently applied to polarimetric data by Vulpiani et al [27] and Montopoli et al [28], is used to define the microphysical characteristics of an ash cloud from radar data. The VARR is based on forward electromagnetic simulations of ash particles in the microwave region assuming a Gamma size distribution model of oblate particles with the random orientation, axis ratio, permittivity and canting angle as specified in [31,32].…”
Section: X-band Radarmentioning
confidence: 99%
“…The rigorous theoretical background regarding the origin of these variables can be found in Bringi and Chandrasekar [2001], while their interpretation with respect to the tephra clouds has been investigated in Vulpiani et al [2011], Montopoli et al [2014a], and Crouch et al [2014]] and will be discussed here in relation to the Etna case study in the following section. The Appendix A in this work summarizes the mathematical definitions of the radar variables used.…”
Section: Radar System Characteristicsmentioning
confidence: 99%
“…Lolli et al (2013) suggested the validation approach for the planned ESA Aeolus mission. Several authors (Burton et al, 2013;Bayat et al, 2013;Nemuc et al, 2013;Montopoli et al, 2014) pointed out that the information brought by multi-wavelength, dualpolarization observations should be further investigated by both experimental data and modeling. In order to consolidate demonstrative results, statistically significant data sets from long time periods (Pichelli et al, 2014) or from dedicated field experiments (Chen et al, 2013) deploying remote sensing observations should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A simple relationship between the reflectivity factor and kinetic energy fluxes is found for each case study. Montopoli et al (2014) discuss the potentiality and drawbacks of X-band dual-polarization (DPX) radar measurements to estimate near-source volcanic ash cloud parameters. They present data acquired during the Grímsvötn (Iceland) volcanic eruptions in May 2011.…”
Section: The Tropospheric Profiling Special Issuementioning
confidence: 99%